DETECTABILITY OF PULMONARY TUBERCULOSIS IN SCHOOLCHILDREN FROM DIFFERENT REGIONS OF THE REPUBLIC OF TAJIKISTAN - U.YU. SIRODJIDINOVA; O.I. BOBOKHODJAEV; K.I. PIROV; F.S. SIRODJIDINOV (Avicenna Tajik State Medical University, 2017)
Objective: To study the infection rate and latent forms of tuberculosis (TB) among the children of school age. Methods: Comparative results of tuberculin diagnostics among children of school age (8-14 years) in Dushanbe (4284 children) and in the rural area of the Dj. Rumi district (1884 children) at the Khatlon region of the Republic of Tajikistan are presented. Results: The obtained data confirm that the infection of children with TB in Dushanbe comprises 10.7% and in rural areas 1,5 times more than urban reaching 16.2%. Patients who have not been previously reported to anti-tuberculosis institutions were detected: in Dushanbe - 4 patients, in the village - 3 patients. The number of identified patients in the recalculation for 100,000 surveyed people in Dushanbe reached 93.2 and in the village it was almost 2 times more - 159.2. Conclusion: One of the main reason is the lack of unregular tuberculin diagnostics, ignorance of BCG revaccination and unawareness of PHC doctors in undetected patients among the schoolchildren.